SOCIAL SECURITY PROCEDURES FOR WORKERS POST WORK ACCIDENT - Asri Pulserimia (Faculty of Law, Khairun University, 2022)
Manpower is an important component for the realization of successful development, during the working period of the workforce must be maintained and respected for their rights, both the rights that are inherent in them since they were born, namely human rights or their rights while at work. The existence of human rights and rights attached to workers from work creates an obligation for those who employ them to provide social security for their workers, in the form of protection, maintenance and improvement of welfare. Social Security, one of which can be in the form of work accident insurance, considering that an accident is something that cannot be calculated, however, there is a clear difference between an accident and a work accident, both in terms of the type of accident, the time it occurred, the place where it occurred, the people affected, and the consequences. With this, social security can provide certainty and understanding for workers who experience work accidents through social security procedures for workers after work accidents.